Legal Protection Of The Beautycian Doctor Profession In Legal Dispute Resolution - Nancy Gunawan; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2024)
Legislation in Indonesia has provided a lot of legal protection for aesthetic doctors in the form of legal protection for the rights of aesthetic doctors starting from the 1945 Constitution of the Republic of Indonesia, the Civil Code, the Criminal Code, the -Consumer Protection Law, Medical Practice Law, Health Law, Hospital Law, Health Personnel Law, and supported in Minister of Health Regulation Number 269/Menkes/Per/III/2008 concerning Medical Records, Regulations Minister of Health Number 290/Menkes/Per/III/2008 concerning Approval of Medical Actions, Minister of Health Regulation No. 36 of 2012 concerning Medical Secrets, Supreme Court Regulation no. 1 of 2016 concerning Mediation Procedures in Court. The role of the Indonesian Doctors Association in supporting the aesthetic doctor profession in resolving legal disputes is as a mediator in selecting expert witnesses. The Indonesian Doctors Association will help its members who are deemed guilty if according to the Indonesian Doctors Association the doctor has carried out procedures in accordance with their professional duties.